Analisis Kreativitas Fisika Siswa dalam Model Pembelajaran Berbasis Masalah Menggunakan Simulasi Virtual - Shinta Mutiara Dewi; Gunawan Gunawan; Ahmad Harjono (Indonesian Publication Center, 2021)
This quasi-experimental research aims to analyze the effect of a problem-based learning (PBL) model assisted by virtual simulation on high school students' physics creativity. The research employed a non-equivalent control group design with a purposive sampling technique at SMAN 2 Mataram. The experimental group implemented the PBL model with virtual simulation, while the control group received direct instruction. Data were collected using essay-based Verbal Creativity Tests (TKV) and Figural Creativity Tests (TKF). The hypothesis test using the polled variance t-test showed that the PBL model assisted by virtual simulation significantly influenced students' physics creativity. The experimental group achieved a higher post-test average score for total creativity (56.96) compared to the control group (49.68). Furthermore, the increase in figural creativity was consistently higher than verbal creativity in both classes. This indicates that students find it easier to express their spatial imagination and divergent solutions through visual representations or drawings rather than verbal arguments when solving physics problems. In conclusion, the PBL model assisted by virtual simulation is effective in enhancing students' creative thinking skills.